Fasciola hepatica Fatty Acid Binding Protein 1 Modulates T cell Polarization by Promoting Dendritic Cell Thrombospondin-1 Secretion Without Affecting Metabolic Homeostasis in Obese Mice - Zawistowska-Deniziak, Anna; Lambooij, Joost M.; Kalinowska, Alicja; Patente, Thiago A.; Łapiński, Maciej; van der Zande, Hendrik J. P.; Basałaj, Katarzyna; de Korne, Clarize M.; Chayé, Mathilde A. M.; Gasan, Thomas A.; Norbury, Luke J.; Giera, Martin; et al. (Frontiers in Immunology, 2022)
Background: The parasitic trematode Fasciola hepatica evades host immune defenses through secretion of various immunomodulatory molecules. Fatty Acid Binding Proteins (fhFABPs) are among the main excreted/secreted proteins and have been shown to display anti-inflammatory properties. However, little is currently known regarding their impact on dendritic cells (DCs) and their subsequent capacity to prime specific CD4+ T cell subsets. Methodology/Principal Findings: The immunomodulatory effects of both native F. hepatica extracts and recombinant fhFABPs were assessed on monocyte-derived human DCs (moDCs) and the underlying mechanism was next investigated using various approaches, including DC-allogenic T cell co-culture and DC phenotyping through transcriptomic, proteomic and FACS analyses. We mainly showed that fhFABP1 induced a tolerogenic-like phenotype in LPS-stimulated moDCs characterized by a dose-dependent increase in the cell-surface tolerogenic marker CD103 and IL-10 secretion, while DC co-stimulatory markers were not affected. A significant decrease in secretion of the pro-inflammatory cytokines IL-12p70 and IL-6 was also observed. In addition, these effects were associated with an increase in both Th2-on-Th1 ratio and IL-10 secretion by CD4+ T cells following DC-T cell co-culture. RNA sequencing and targeted proteomic analyses identified thrombospondin-1 (TSP-1) as a non-canonical factor highly expressed and secreted by fhFABP1-primed moDCs. The effect of fhFABP1 on T cell skewing was abolished when using a TSP-1 blocking antibody during DC-T cell co-culture. Immunomodulation by helminth molecules has been linked to improved metabolic homeostasis during obesity. Although fhFABP1 injection in high-fat diet-fed obese mice induced a potent Th2 immune response in adipose tissue, it did not improved insulin sensitivity or glucose homeostasis. Conclusions/Significance: We show that fhFABP1 modulates T cell polarization, notably by promoting DC TSP-1 secretion in vitro, without affecting metabolic homeostasis in a mouse model of type 2 diabetes.